Comparison of Online Dispute Resolution for Business Disputes in Indonesia and The United States - Opniel Harsana B Pongkapadang; Winner Sitorus; Hasbir Paserangi Paserangi; Nabeel Mahdi Althabhawi; Aneesh V. Pillai (Universitas Negeri Semarang, 2026)
This article examines the regulatory comparison and legal framework of Online Dispute Resolution (ODR) in Indonesia and the United States, highlighting key differences in regulatory integration, technological infrastructure, and institutional synergy. The main problem identified is the fragmentation of ODR regulations in Indonesia, which lacks a comprehensive legal framework and faces significant challenges in ensuring legal certainty, effective enforcement, and public trust, especially among micro, small, and medium-sized enterprises. This study aims to analyze the weaknesses and strengths of ODR systems in both countries and formulate strategic recommendations for developing a credible and adaptive ODR ecosystem in Indonesia. Employing a normative legal research method with a statute and analytical comparative approach, the study explores the regulatory basis, implementation models, and best practices from both jurisdictions. The findings show that the United States has successfully developed an integrated legal structure for ODR, supported by federal acts, technological innovations, and multi-stakeholder collaboration, which ensures enforcement and data protection. In contrast, Indonesia's ODR implementation is still hindered by sectoral regulations, limited digital literacy, and the absence of standard accreditation for online mediators and arbitrators. The analysis concludes that Indonesia urgently needs an integrated ODR law that includes clear definitions, standard operating procedures, accreditation requirements, and mechanisms for the recognition and enforcement of ODR decisions in the national judiciary. By adopting best practices from the United States, particularly regarding cross-sector integration, technological adaptation, and decision enforceability, Indonesia can strengthen its ODR framework to support fair, efficient, and reliable business dispute resolution in the digital era.